Gelingende Geburt interdisziplinäre Erkundungen in umstrittenen Terrains - Mitscherlich-Schönherr, Olivia 1973-; Anselm, Reiner 1965- (Grenzgänge, 2021)
Birth is a natural and unambiguous phenomenon, yet it is open to multiple interpretations. Does an infant first enjoy an autonomous right to life upon birth? What makes a birth successful? Should pregnancy and birth be viewed as normative, or do they demand a phenomenologically oriented approach? The volume uses an interdisciplinary perspective to examine different ways of understanding this basic fact of human existence